Influence of Different Atomic Percentage of Silver Doped Nano Zinc Oxide on Titanium Dioxide Seeded Substrate - Zulaikha Umbaidilah, Siti; Amierah M. Asib, Nur; Afaah Abdullah, Nurul; Rusop, Mohamad; Khusaimi, Zuraidah (International Journal of Engineering and Technology, 2019)
Non-doped ZnO/TiO2 and Silver (Ag) doped ZnO/TiO2 nanostructures thin film were successfully synthesized on glass substrate by using sol-gel spin coating technique for deposition of TiO2 seed layer and solution immersion method for growth of Ag-doped ZnO/TiO2 nanostructure. Different atomic percentage (at%) which is 0.5, 1.0, 1.5, 2.0 and 2.5 at% of Ag doped were added in 0.4 M of Zn2+ solution. The EDX result revealed that the sample was composed of Zn, O and Ag elements which confirmed the existence of Ag element in the sample. The XRD spectra shows that the intensity of the (002) peak of 0.5 at % Ag-doped ZnO/TiO2 was the highest compared to other samples and all the samples revealed polycrystalline structure belonging to the ZnO hexagonal wurtzite type. The UV-vis absorbance also indicates that 0.5 at% Ag-doped ZnO/TiO2 has the highest absorbance and non-doped ZnO/TiO2 displayed the lowest absorbance compared to the other sample. Thus, 0.5 at% of Ag-doped ZnO/TiO2 is the best candidate for optical application due to the higher intensity and greater absorbance.Â Â